2015
DOI: 10.1111/jfpp.12466
|View full text |Cite
|
Sign up to set email alerts
|

Production and Functional Evaluation of a Protein Concentrate from Giant Squid (D osidicus gigas ) Fins Obtained by Alkaline Dissolution

Abstract: Two protein concentrates from jumbo squid fins (Dosidicus gigas) were elaborated. One of them was obtained via alkaline dissolution and subsequent isoelectric precipitation (alkaline protein concentrate [APC]) and the other was obtained via the traditional method (neutral protein concentrate [NCP]). The electrophoretic profile of the APC showed that the myosin heavy chain band disappeared, mainly due to the denaturation induced by alkaline solubilization or activation of alkaline protease. Concerning the quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Márquez‐Álvarez et al . () compared and evaluated the functional properties of the protein concentrates obtained from squid fins via alkaline dissolution and subsequent isoelectric precipitation and the conventional methodology (water washing muscle). The electrophoretic profile of the alkaline concentrate showed that the myosin‐heavy‐chain band disappeared, mainly due to the denaturation induced by alkaline solubilisation or activation of alkaline protease.…”
Section: Bioactive Compounds From Fins Tentacles Arms and Headsmentioning
confidence: 99%
“…Márquez‐Álvarez et al . () compared and evaluated the functional properties of the protein concentrates obtained from squid fins via alkaline dissolution and subsequent isoelectric precipitation and the conventional methodology (water washing muscle). The electrophoretic profile of the alkaline concentrate showed that the myosin‐heavy‐chain band disappeared, mainly due to the denaturation induced by alkaline solubilisation or activation of alkaline protease.…”
Section: Bioactive Compounds From Fins Tentacles Arms and Headsmentioning
confidence: 99%